ANALISIS PENERAPAN LITERASI MEMBACA MELALUI KEGIATAN POJOK BACA DI KELAS RENDAH SEKOLAH DASAR - Miftahul Jannah; Haifaturrahman, Haifaturrahman; Nursina Sari, Nursina Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of reading literacy through the “reading corner” activity among lower-grade elementary school students. The background of this research is based on the low reading interest of elementary school students, which requires early habituation strategies to foster reading habits. The study employs a descriptive qualitative approach with participants consisting of second-grade students from a public elementary school selected through purposive sampling. Data were collected through classroom observations of reading corner activities, interviews with teachers and students, and documentation such as activity photos and book collection lists. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the reading corner contributes positively to increasing students’ reading interest and motivation, enriching their vocabulary, and developing independent reading habits. However, several challenges were identified, including limited book variety, students’ lack of discipline in maintaining reading materials, and insufficient teacher follow-up. Overall, the reading corner is proven to be an effective strategy for promoting a culture of reading literacy in lower elementary classrooms, particularly when managed consistently with adequate facilities and teacher creativity.